Binary spatial amplitude modulation of continuous transverse modal electric field using a single lens for mode selectivity in multimode fiber - Amphawan, Angela (Taylor & Francis Group, 2012)
The demand for portable real-time optical applications such as medical optical sensors and optical transceivers instigate the need for compact optical designs.The aim of this paper is to demonstrate a new, compact design for binary spatial amplitude modulation in a multimode fiber-based optical transceiver, adapted from microscopy.The continuous-amplitude transverse modal electric field of an infinite parabolic multimode fiber is retrieved from a binary amplitude-modulated field using a single lens.The retrieved field is in good agreement with the original modal electric field.